2011
DOI: 10.1080/02678292.2010.550326
|View full text |Cite
|
Sign up to set email alerts
|

New symmetric azomethinic dimer: the influence of structural heterogeneity on the liquid crystalline behaviour

Abstract: The paper deals with the study of the thermotropic liquid crystalline properties of a new azomethinic symmetric dimer and some of its structural heterogeneous mixtures with one of its reagents. Their thermotropic behaviour was monitored by polarised light microscopy, differential scanning microscopy and variable temperature X-ray diffraction measurements. The influence of the structural heterogeneity on the mesomorphic behaviour was established and some similarities with the mesomorphic behaviour of the polydi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In particular, liquid crystal dimers proved to be a rich source of new types of intercalated smectic phases (see, for example,references [8][9][10][11][12]) and, rare and unusual phase transition sequences (see, for example, references [13,14]). More recently, interest has focussed on, for example, their flexoelectric behaviour, [15][16][17] T-and H-shaped dimers, [18][19][20][21] non-alkyl spacers, [22][23][24] cholesterylbased dimers, [25][26][27][28][29][30] discotic dimers, [31][32][33] carbohydrate-based dimers, [34] bent core-calamitic nonsymmetric dimers, [35,36] the effects of linking groups, [37] dimers containing new types of mesogenic units and functionalities, [38][39][40][41][42][43][44][45][46] as well as on higher oligomers. [47][48][49][50] Perhaps the most exciting recent discovery involving liquid crystal dimers, however, has been the observation of nematic-nematic transitions for a small number of odd-membered dimers.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, liquid crystal dimers proved to be a rich source of new types of intercalated smectic phases (see, for example,references [8][9][10][11][12]) and, rare and unusual phase transition sequences (see, for example, references [13,14]). More recently, interest has focussed on, for example, their flexoelectric behaviour, [15][16][17] T-and H-shaped dimers, [18][19][20][21] non-alkyl spacers, [22][23][24] cholesterylbased dimers, [25][26][27][28][29][30] discotic dimers, [31][32][33] carbohydrate-based dimers, [34] bent core-calamitic nonsymmetric dimers, [35,36] the effects of linking groups, [37] dimers containing new types of mesogenic units and functionalities, [38][39][40][41][42][43][44][45][46] as well as on higher oligomers. [47][48][49][50] Perhaps the most exciting recent discovery involving liquid crystal dimers, however, has been the observation of nematic-nematic transitions for a small number of odd-membered dimers.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest oligomers, termed liquid crystal dimers, contain just two liquid crystal units interconnected by a single spacer and these have been by far the most widely studied oligomers [2,3] although higher oligomers such as trimers and tetramers have been reported (for recent examples, see [5][6][7][8][9]). The intense interest in liquid crystal dimers has arisen because they exhibit very different properties to conventional low molar mass liquid crystals and recent investigations have included the observation of nematic-nematic transitions [10][11][12][13]; siloxanebased dimers [14]; studies of their light emitting [15] and flexoelectric properties [16,17]; the effects of spacer length and linking groups [18,19]; bent corecalamitic dimers [20,21]; anthracene-based [22] and discotic dimers [23]; H-shaped [24,25] and cyclic dimers [26]; intercalated [27,28] and biaxial smectic phases [29]. and compared their properties to those of the corresponding dimers containing a conventional alkyl spacer [31,32]:…”
Section: Introductionmentioning
confidence: 99%
“…The resulted mesophase, named plastic mesophase, was observed for many types of rigid or semiflexible polymers (32)(33)(34). Besides, a systematic study on dimeric model compounds indicated the influence of polydispersity on its occurrence (35). In the cooling score, the mesophase did not appear, the most probably because of crosslinking, which generated a large rigid network.…”
mentioning
confidence: 93%